The Steaks Are High: COVID-19’s Impact on Direct-To-Consumer Marketing in the Oklahoma Beef Industry - Linnea Langusch; Dwayne Cartmell; Quisto Settle (Journal of Applied Communications, 2023)
The COVID-19 pandemic encouraged some beef producers to market their products directly to consumers. For many consumers the idea of buying beef products from local sources is appealing. Relationship management theory framed this study, as beef producers used relationship building as a path to product promotion. This study explored Oklahoma beef producers’ perceptions of changes that have occurred in direct-to-consumer marketing and consumer communications in the beef industry during the COVID-19 pandemic using semi-structured interviews. This study consisted of 16 participants found via snowball sampling. Participants were Oklahoma cattle ranchers over 18 years old who used one or more channels of direct marketing to sell beef products to consumers. Findings indicate beef producers focused on creating and maintaining relationships with customers. Many producers used social media to connect with customers due to the absence of in-person opportunities. Word-of-mouth marketing through social media and local communities brought in new customers, and as producers invested in maintaining authentic relationships with their customers, they saw increased customer loyalty. Producers focused on sharing the 'story behind the beef’ to increase trust and openness in their communications with consumers. Most producers who used social media did not strategize when posting. Some producers failed to adapt to consumer needs during the pandemic and did not use social media at all which limited their customer interactions. Future research could explore consumer perceptions of beef producers during the COVID-19 pandemic to compare and assess the effectiveness of the communications between these two groups.
Keywords: COVID-19; beef; relationships; direct marketing; local food